Comparison of Efficiency of Intermaxillary Fixation Screws Versus Erich Arch Bars for Maxillomandibular Fixation in Maxillofacial Trauma: Intermaxillary Fixation Screws Versus Erich Arch Bars for Maxillomandibular Fixation - Khalil, Muhammad; Akhtar, Uzair Bin; Akram, Komal; Khawaja, Mustafa Ayub; Jabbar, Maria; Tufail, Ifra (Pakistan Journal of Health Sciences, 2026)
Maxillomandibular fixation (MMF) is a popular intervention tool for maxillofacial fractures. Erich arch bars are used historically, but intermaxillary fixation screws provide some potential benefits, including less time in surgery and better oral health. Objective: To compare the Erich arch bar with intermaxillary fixation screws in maxillomandibular fixation in facial fractures. Methods: This prospective comparative trial was carried out in Sharif Medical and Dental College and involved 60 patients who needed maxillomandibular fixation after maxillofacial trauma. There were two groups of patients: intermaxillary fixation screws (n=30) and Erich arch bars (n=30). The assessment of the post-operative occlusal stability, duration of the surgery, and the assessment of oral hygiene based on the Oral Hygiene Index were performed with the help of SPSS version 23.0. Results: The intermaxillary fixation screw group showed a shorter surgical time, as well as superior oral hygiene (p<0.05). The groups did not show any significant difference in the postoperative occlusal stability (p=0.389). Conclusion: intermaxillary fixation screws offer similar occlusion potentialities at lower operative duration and with improved oral health as compared with Erich arch bar.